THE USE OF PREFIXES AND SUFFIXES FOR INCREASING VOCABULARY STUDENTS - Aslamiah, Suaibatul (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2020)
A prefix is a word or letter. And also, a prefix is a letter or a group of letters added to the beginning of a word to make a new word. Every prefix has its own meaning. An English word can consist of three parts: the root, a prefix, and a suffix. A suffix is a word element that is placed after the root. The suffixes changes the word’s meaning as well as its function (use). Vocabulary is one element for communicating or sharing idea. A vocabulary is important, it is not only to read or write. The students who have adequate vocabulary will easy to understand and support the carrier in the future. Moreover, the students who have good skill absolutely fast to adapt with the international global era situation.